Canadian Home Total Parenteral Nutrition Registry: Preliminary Data on the Patient Population - Maitreyi Raman; Leah Gramlich; Scott Whittaker; Johane P Allard (Canadian Journal of Gastroenterology)
BACKGROUND: Long-term administration of home total parenteral nutrition (HTPN) has permitted patients with chronic intestinal failure to survive for prolonged periods of time. However, HTPN is associated with numerous complications, all of which increase morbidity and mortality. In Canada, a comprehensive review of the HTPN population has never been performed.